KADAR SAPONIN SIRSAK (Anona muricata L.) BERDASARKAN TINGKAT KEMATANGAN DAUN - Patrecia Elfien Malaihollo; Ritha Lusian Karuwal; Hermalina Sinay (Universitas Lambung Mangkurat, 2026)
Soursop (Annona muricata L.) is a plant species belonging to the Annonaceae family that is used as a traditional medicinal plant. Generally, the part utilised for medicinal purposes is the leaf. This is because the leaves contain a high concentration of secondary metabolites, one of which is saponin. The content of secondary metabolites can vary depending on the maturity of the leaves. This study was conducted to determine the saponin content in soursop leaves based on their maturity level. The research utilised leaves at young, medium and mature stages, with each stage tested three times. The analysis was conducted both qualitatively and quantitatively. The results of the qualitative test indicated that leaves at different maturity levels tested positive for saponins, as indicated by the presence of foam. The saponin content found in leaves at the young, medium and mature stages was 4.3653±0.14%; 4.5473±0.09%; and 5.1143±0.078%, respectively. These results indicate that the more mature the leaves, the higher the saponin content.